Spectrophotometric Determination of Nickel(II) with Phenanthrenequinone Monosemicarbazone - Rai, H.C.; Kumar, Ashwini; Singh, K.B.; Kumar, Raman (Asian Journal of Chemistry, 2012)
In the present study, spectrophotometric estimation of nickel(II) with phenanthrenequinone monosemicarbazone (PQSC) have been carried out. Nickel(II) instantaneously gives orange coloured complex on the addition of phenanthrenequinone monosemicarbazone solution. The pH, the concentration range of nickel for adherence to Beer's law and the ratio of nickel to PQSC present in the complex have been determined. Effect of foreign ions on the determination of nickel has also been investigated.